PAJERO INOVASI PENGAWET ALAMI UNTUK IKAN DARI LIMBAH JERAMI - Lisniawati Lisniawati; Yaahani Ayu Sholihah; Cristin Hudoyo; Rahmawati Ariyan Chandra; Mieke Dwi Erfani; Arum Suproborini (EnviroScienteae, 2019)
Straw is a by-product of agricultural business in the form of stem stems and leaves of rice plants. Seeds contain cellulose, hemicellulose, Lignin, phenolic, and carbon. Phenolic and carbon content function as preservatives, antioxidants, disinfectants, and biopesticides. The aim of this PKM is to make the latest innovations of natural preservatives that are safe for health. Implementation method used in this program is the planning, product manufacturing,  promotion stage, and evaluation phase with. We have marketed "PAJERO" in Pacitan district especially in Tamperan fish auction area. We have also collaborated in marketing with UPT P2SKP, seafood stall entrepreneurs and TPI Tamperan fishermen. In Madiun area we have also cooperated with Arnie's fresh fish kiosk in Bunderan Banjarejo, Taman Regency, Madiun District and we also do marketing at the Kojo market in the city of Madiun and we have marketed it through online media namely Instagram and Facebook. Until now we have sold a number of 12 bottles of preservative "PAJERO". The benefit of this PKM is to help fishermen to preserve fish with preservatives that are safe for health These outputs from Pkm are natural fish preservative products, progress reports, final reports, the publication of articles in national scientific journals.